Cyber-Communication: Strategies To Establish Mutually Beneficial Cooperative Relationships - P S Kurniati; F Octa; C Andreani; R Rahayu (International Journal of Education, Information Technology, and Others, 2021)
This study aims to describe and facilitate how to communicate remotely using the internet and establish mutually beneficial cooperation within a company. This research design uses a descriptive method that is supported by conducting surveys and interviews. The population of this study are business owners who are still running in the city of Bandung. The data was collected using survey techniques for business owners who use virtual world communication to interact and interview. The results showed the effectiveness of long distance communication using technology and the internet for business purposes. The criteria studied were the use of cyber communication technology in businesses, companies that are still active, and companies that are self-managed. This research shows that increasingly sophisticated technology makes various jobs more accessible and more practical to communicate and add relationships easily for the progress of a company. The progress of a company can be assessed from the communication design used by a company. Communication without any distance restrictions will help maintain relationships and cooperation between companies